1999
DOI: 10.1021/ja982980h
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Secondary Structure on the Fragmentation of Protonated Peptides

Abstract: The influence of acid−base interactions on the gas-phase dissociation of a series of protonated peptides was investigated. Peptides containing both acidic residues [aspartic (D), glutamic (E), and cysteic acid (C*)] and basic residues [arginine (R)] were dissociated by different activation methods that allow different time frames for dissociation. The synthetic peptides investigated differ systematically in the number and position of arginine residue(s) and include R LDIFSDF R , R LEIFSEF R , R LDIFSDF, LDI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

15
426
1

Year Published

2000
2000
2008
2008

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 339 publications
(442 citation statements)
references
References 112 publications
15
426
1
Order By: Relevance
“…The b 3 ion (m/z 405) is also produced, but in very low abundance (Figure 4c). Tsaprailis et al [21] reported that collisional activation of protonated peptide ions containing arginine and aspartic acid or glutamic acid residues results in selective cleavages at the C-terminal side of the acidic residues if the number of ionizing protons does not exceed the number of arginine residues. Our data with the [M ϩ H] ϩ ion of the PRCGVPDVA appear not to be consistent with this view because the selective cleavage occurs at the amide bond between valine and proline, which gives the b 5 ion.…”
Section: Prcgvpdva Prc(so 2 H)gvpdva and Prc(so 3 H)gvpdvamentioning
confidence: 99%
“…The b 3 ion (m/z 405) is also produced, but in very low abundance (Figure 4c). Tsaprailis et al [21] reported that collisional activation of protonated peptide ions containing arginine and aspartic acid or glutamic acid residues results in selective cleavages at the C-terminal side of the acidic residues if the number of ionizing protons does not exceed the number of arginine residues. Our data with the [M ϩ H] ϩ ion of the PRCGVPDVA appear not to be consistent with this view because the selective cleavage occurs at the amide bond between valine and proline, which gives the b 5 ion.…”
Section: Prcgvpdva Prc(so 2 H)gvpdva and Prc(so 3 H)gvpdvamentioning
confidence: 99%
“…Other alternative ion structures can be derived if His, Arg, Asp, or Lys occupies the C-terminal position in b ions [23][24][25][26]. In these cases the side-chain nucleophiles of the preceding amino acids are responsible for cleavage of the amide bond or reisomerization of the primarily formed oxazolone ring.…”
mentioning
confidence: 99%
“…Statistical [19 -24] and mechanistic [25][26][27][28][29][30][31][32] analyses have led to a better understanding of peptide fragmentation behavior. Specifically, these studies have revealed residuespecific preferential cleavage N-terminal to proline (Pro), C-terminal to aspartic acid (Asp) and glutamic acid (Glu), and C-terminal to oxidized cysteine (e.g., cysteine sulfinic acid and cysteine sulfonic acid) [19,20,[33][34][35][36][37][38][39][40][41][42][43].…”
mentioning
confidence: 99%